Effect of water extract of buckwheat plant seeds Fagopyrum esculentum and ring Trigonella foenum-graecum in the vitality of the initial nodules of Echinococcus granulosus of sheep origin in vitro - Arqem Mesbah; Emad Albadrani; Ibraheem Abdullah (College of Education for Pure Sciences, 2008)
ABSTRACT The results of this study revealed significat inhibitory effect of the aqueous extracts of the seeds of the buckwheat, Fagopyrum esculentum and the fenugreek, Trigonella foenum-graecum on the viability of the protoscleces of Echinococcus granulosus in concentrations of 25 mg/ml, 50 mg/ml, and 75 mg/ml in the periods of 15, 30, and 45, minutes in vitro. Herein, the concentration of 75 mg/ml of the buckwheat inhibited the viability of the protoscoleces completetly in a period of 45 minutes.In general, the effect of the extracts of both seeds increased proportionally with the increase in concetration and the increase in the period of exposure, By the sametoken, the effect of the buckwheat was higher than that of the fenugreek on the viability of the protoscoleces of E. granulosus in vitro.